I, robot - Asimov, Isaac, 1920-1992 (Harper Voyager, 2018)
Earth is ruled by master-machines but the Three Laws of Robotics have been designed to ensure humans maintain the upper hand: 1) A robot may not injure a human being or allow a human being to come to harm 2) A robot must obey orders given to it by human beings except where such orders would conflict with the First Law. 3) A robot must protect its own existence as long as such protection does not conflict with the First or Second Law. But what happens when a rogue robot's idea of what is good for society contravenes the Three Laws?